Toán Lớp 8: a)3/(x-7)+3/(x-7)+(-5)/(x^2-49) b)4/(x+2)+2/(x-2)+8/(4-x^2 )a)3/(x-7)+3/(x-7)+(-5)/(x^2-49)

Toán Lớp 8: a)3/(x-7)+3/(x-7)+(-5)/(x^2-49)
b)4/(x+2)+2/(x-2)+8/(4-x^2 )a)3/(x-7)+3/(x-7)+(-5)/(x^2-49)

0 bình luận về “Toán Lớp 8: a)3/(x-7)+3/(x-7)+(-5)/(x^2-49) b)4/(x+2)+2/(x-2)+8/(4-x^2 )a)3/(x-7)+3/(x-7)+(-5)/(x^2-49)”

  1. a)3/(x-7)+3/(x-7)+(-5)/(x^2-49)=3/(x-7) +3/(x-7)+(-5)/(x-7)*(x+7)=3*(x+7)/(x-7)*(x+7) +3*(x+7)/(x+7)*(x-7)+(-5)/(x-7)*(x+7)=(3*(x+7)+3*(x+7)-5)/(x-7)*(x+7)=3x+21+3x+21-5/(x-7)*(x+7)=6x+37/(x-7)*(x+7)
    b)4/(x+2)+2/(x-2)+8/(4-x^2)=4/(x+2)-2/(2-x)+8/(2-x)*(2+x)=4*(2-x)/(x+2)*(2-x)-2*(2+x)/(2-x)*(2+x)+8/(2-x)*(2+x)=(4*(2-x)-2*(2+x)+8)/(2-x)*(2+x)=8-4x-4-2x+8/(2-x)*(2+x)=-6x+12/(2-x)*(2+x)=
    6(-x+2)/(2-x)*(2+x)=6/2+x
    Còn câu C giống câu a nha

Viết một bình luận